The Impact of Anlotinib on Brain Metastases of Non‐Small Cell Lung Cancer: Post Hoc Analysis of a Phase III Randomized Control Trial (ALTER0303). (20th February 2020) - Jiang, Shunjun; Liang, Hengrui; Liu, Zhichao; Zhao, Shen; Liu, Jun; Xie, Zhanhong; Wang, Wei; Zhang, Yalei; Han, Baohui; He, Jianxing; Liang, Wenhua
Abstract: Background: Anlotinib has been shown to prolong progression‐free survival (PFS) and overall survival (OS) for non‐small cell lung cancer (NSCLC). Herein we sought to analyze the effect of anlotinib in managing brain metastases (BM) and its brain‐associated toxicities. Methods: The PFS and OS of anlotinib versus placebo in those with and without BM recorded at baseline were calculated and compared respectively. Time to brain progression (TTBP), a direct indicator of intracranial control, was also compared between anlotinib and placebo. All calculations were adjusted for confounding factors, including stage, histology, driver mutation type, and therapy history. Results: A total of 437 patients were included; 97 cases were recorded with BM at baseline. For patients with BM at baseline, anlotinib was associated with longer PFS (hazard ratio [HR], 0.29; 95% confidence interval [CI], 0.15–0.56) and OS (HR, 0.72; 95% CI, 0.42–1.12), presenting similar extent of improvement in those without BM (PFS: HR, 0.33; 95% CI, 0.24–0.45; OS: HR, 0.67; 95% CI, 0.50–0.91). Specifically, the intracranial objective response rate was 14.3% and the disease control rate was 85.7% in patients with BM who were treated with anlotinib. Anlotinib was associated with longer TTBP (HR, 0.11; 95% CI, 0.03–0.41; p = .001) despite all confounders. Additionally, anlotinib was associated with more neural toxicities (18.4% vs. 8.4%) and psychological symptoms (49.3% vs. 35.7%) but not with infarction or cerebral hemorrhage. Conclusion: Anlotinib can benefit patients with advanced NSCLC with BM and is highly potent in the management of intracranial lesions. Its special effect on BM and cerebral tissue merits further investigation. (ClinicalTrials.gov ID: NCT02388919). Abstract : Anlotinib, a novel multi‐targeted tyrosine kinase inhibitor, has a broad spectrum of inhibitory action on tumor angiogenesis. This article reports results of a phase III trial that explored whether anlotinib is effective for intracranial lesions in advanced non‐small cell lung cancer and evaluated the effect of anlotinib in managing brain metastases and its brain‐associated toxicities.